Ethnic differences and heritability of blood pressure circadian rhythm in African and European American youth and young adults. Issue 1 (January 2022) - Xu, Yanyan; Su, Shaoyong; Brown, Michelle; Snieder, Harold; Harshfield, Gregory; Wang, Xiaoling
Abstract : N/A: Background: The aim of this study was to investigate whether blood pressure (BP) circadian rhythm in African Americans differed from that in European Americans. We further examined the genetic and/or environmental sources of variances of the BP circadian rhythm parameters and the extent to which they depend on ethnicity or sex. Method: Quantification of BP circadian rhythm was obtained using Fourier transformation from the ambulatory BP monitoring data of 760 individuals (mean age, 17.2 ± 3.3; 322 twin pairs and 116 singletons; 351 African Americans). Results: BP circadian rhythm showed a clear difference by ethnic group with African Americans having a lower amplitude ( P  = 1.5e–08), a lower percentage rhythm ( P  = 2.8e–11), a higher MESOR ( P  = 2.5e–05) and being more likely not to display circadian rhythm ( P  = 0.002) or not in phase ( P  = 0.003). Familial aggregation was identified for amplitude, percentage rhythm and acrophase with genetic factors and common environmental factors together accounting for 23 to 33% of the total variance of these BP circadian rhythm parameters. Unique environmental factors were the largest contributor explaining up to 67--77% of the total variance of these parameters. No sex or ethnicity difference in the variance components of BP circadian rhythm was observed. Conclusion: This study suggests that ethnic differences in BP circadian rhythm already exist in youth with African Americans having a dampened circadian rhythm and better BP circadian rhythm may be achieved by changes in environmental factors. Abstract : Supplemental Digital Content is available in the text